FAST FASHION AND ITS IMPACT ON THE ENVIRONMENT: AN OVERVIEW - Mishra, Pratibha; Yadav, Madhura (The journal of contemporary issues in business and government, 2022)
The fashion industry has undergone significant transformation, specifically in the last two decades. Fashion industry changes have forced manufacturers to seek low cost and multiple options in design, as well as quick to market, which are crucial strategies for maintaining a beneficial position in an increasingly globally competitive market. The purpose of this article to review the literature on changes that have taken place in the fashion apparel industry since the 1990s, with particular emphasis placed on the development of the concept of "throwaway" or "fast fashion." It provides an overview of fast fashion v/s sustainable fashion from both a supplier and a consumer's point of view, and it attracts attention to a number of potential research questions.